Tales of the Sunshine Coast - Wood, Alf, 1905- (Spring Hill, Qld. : Boolarong Publications, 1982)
Segments on the Kabi tribe; stories; meanings of place names.
Cover subtitle: Dreamtime to now.
Keywords: Australian Aboriginal tales & legends. Queensland. Sunshine Coast. Texts; Aboriginal Australians -- Queensland -- Sunshine Coast -- Folklore; Gubbi Gubbi / Kabi Kabi / Gabi Gabi people (E29) (Qld SG56-06); Sites - Dreaming tracks; Language - Vocabulary - Place names; Stories and motifs; Glass House Mountains (SE Qld SG56-15); Maroochy River / Maroochydore (SE Qld SG56-10); Bribie Island (SE Qld SG56-15, SG56-10); South East Queensland (SE Qld SG56, SH56); Noosa / Tewantin (SE Qld SG56-10); Mudjimba Island (SE Qld SG56-10); Peregian Beach (SE Qld SG56-10); Coolum Beach (SE Qld SG56-10)